IMPLEMENTASI PEMBELAJARAN BAHASA JAWA SD YANG INTEGRATIF KOMUNIKATIF BERBASIS FOLKLORE LISAN SEBAGAI WUJUD KONSERVASI BUDAYA - Kurniati, Endang (Universitas Negeri Semarang, 2015)
This research objective was to disseminate and to test the effectiveness of the design of integrative communicative Javanese language learning in elementary school based on verbal folklore as a form of cultural conservation. This research used experimental research method. The subjects of this research were elementary school teachers and students in Semarang and Banyumas. The result of this research showed that this learning design was effective. The students’ result of study in experimental class was better compared with control class and students’ performance in experimental class during the learning process was more active, enthusiastic, and creative. According to the teachers, this learning besides teaching language, art, and culture was also educating character as well. Moreover, this learning was as alternative of Javanese culture preservation.Keywords: integratif, komunikatif, folklore lisan, konservasi budaya